The structure and construction principles of the universal MIS for tasks of the evidence-based medicine - Моторний, Анатолій Павлович (Eastern-European Journal of Enterprise Technologies, 2012)
The article deals with the problem of developing a universal medical information system for the optimization of the individuals engaged in tasks of EBM. The necessity of developing and implementing this system, proposed its structure and working principle